2005
DOI: 10.1021/es047987f
|View full text |Cite
|
Sign up to set email alerts
|

Congener-Specific Tissue Distribution of Aroclor 1254 and a Highly Chlorinated Environmental PCB Mixture in Rats

Abstract: Polychlorinated biphenyl (PCB) mixtures were synthesized and marketed in Eastern European countries, but little is known abouttheir composition, distribution, ortoxicity. PCB-contaminated soil from the former production site of the Polish PCB mixture Chlorofen was collected, and the PCBs were extracted. An in vivo study was performed to investigate the PCB tissue distribution and biochemical effects of this soil extract in immature male Sprague-Dawley rats. Rats were administered 0.05 mmol/kg soil-extracted PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…Aroclor 1254 and a soil extract of Chlorofen). Our previous work has shown that exposure to these two PCB mixtures causes the induction of hepatic enzymes in laboratory animals (26). Specifically, we have shown that Aroclor 1254-treated rats have elevated EROD (CYP 1A) activity and rats treated with a soil extract of Chlorofen have elevated PROD (CYP 2B) activity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Aroclor 1254 and a soil extract of Chlorofen). Our previous work has shown that exposure to these two PCB mixtures causes the induction of hepatic enzymes in laboratory animals (26). Specifically, we have shown that Aroclor 1254-treated rats have elevated EROD (CYP 1A) activity and rats treated with a soil extract of Chlorofen have elevated PROD (CYP 2B) activity.…”
Section: Introductionmentioning
confidence: 87%
“…that higher chlorinated PCBs (for example PCB 174, 180, 193, 194 and 203+196) appear to be selectively retained in the spleen of both treatment groups (26). We analyzed statistically significant differences in the EFs among different tissues (Tables 2 and 3) to determine if the same observation can also be made for the tissue specific disposition of PCB atropisomers.…”
Section: Comparison Of the Efs Of Pcbs In Tissues From Both Treatmentmentioning
confidence: 98%
“…The PCB extract was concentrated to 1 mL and an internal standard solution consisting of PCBs 30 and 204 (300 μL; 100.8 μg PCB/L in hexane) was added. Sulfur impurities were removed using standard EPA procedures prior to PCB analysis (Kania-Korwel et al 2005;Kania-Korwel et al 2007;Lehmler et al 2003). …”
Section: Pcb Analysismentioning
confidence: 99%
“…The PCB analysis was performed using a HP 6890 gas chromatograph with 60-m DB-5 capillary column and a 63 Ni μ-ECD detector (Kania-Korwel et al 2005). The detector temperature was 300°C.…”
Section: Pcb Analysismentioning
confidence: 99%
“…Typically, less-chlorinated PCBs (≤5 Cl) have a more rapid uptake (Oberg et al, 2002) and are more rapidly metabolized and eliminated (Matthews and Anderson, 1975;Oberg et al, 2002) than higher-molecular-weight congeners. Upon exposure, however, these compounds may be initially high in perfused tissue (Kania-Korwell et al, 2005) so that alewife from the ISC had a PCB profile indicative of parent PCB, e.g., Aroclor 1242.…”
Section: Discussionmentioning
confidence: 99%